A dynamic perspective on L2 pronunciation development: bridging research and communicative teaching practice - Lima Jr, Ronaldo Mangueira (2019)
The main goal of this paper is to raise language teachers’ awareness of the need to incorporate research-based pronunciation teaching into their communicative language classes in an ongoing and integrated manner. To do so, we begin by characterizing language and its learning process as dynamic systems, which develop over time through the constant interaction of their agents. Then we review current studies on L2 sound production and perception as well as on the explicit teaching of L2 pronunciation under a dynamic perspective in the Brazilian scenario. Finally, we suggest a few general directions and guiding principles for pronunciation teaching, showing that it is possible to include pronunciation instruction in communicative language teaching.